Bacterial aerobic synthesis of nanocrystalline magnetite - Bharde, Atul A.; Wani, A.; Shouche, Y.; Joy, Pattayil Alias; Bhagavatula L. V. Prasad; Sastry, M. (Journal of the American Chemical Society, 2005)

Biological synthesis of stable vaterite crystals by the reaction of calcium ions with germinating chickpea seeds - Rautaray, D.; Sanyal, A.; Bharde, Atul A.; Ahmad, Absar; Sastry, M. (Crystal Growth & Design, 2005)
The total biological synthesis of CaCO3 crystals of the metastable vaterite polymorph at room temperature by simple protein-mediated reaction of aqueous Ca2+ ions with the CO2 generated during the root growth from germinating chickpea (Cicer arietinum) seeds is described. Highly stable vaterite crystals of spherical morphology are obtained, indicating that the proteins secreted from the roots during growth play a crucial role in stabilizing and directing the crystal growth.

Biosynthesis of gold and silver nanoparticles using emblica officinalis fruit extract, their phase transfer and transmetallation in an organic solution - Ankamwar, Balaprasad; Damle, C.; Ahmad, Absar; Sastry, M. (Journal of Nanoscience and Nanotechnology, 2005)
The design, synthesis and characterization of biologically synthesized nanomaterials have become an area of significant interest. In this paper, we report the extracellular synthesis of gold and silver nanoparticles using Emblica Officinalis (amla, Indian Gooseberry) fruit extract as the reducing agent to synthesize Ag and Au nanoparticles, their subsequent phase transfer to an organic solution and the transmetallation reaction of hydrophobized silver nanoparticles with hydrophobized chloroaurate ions. On treating aqueous silver sulfate and chloroauric acid solutions with Emblica Officinalis fruit extract, rapid reduction of the silver and chloroaurate ions is observed leading to the formation of highly stable silver and gold nanoparticles in solution. Transmission Electron Microscopy analysis of the silver and gold nanoparticles indicated that they ranged in size from 10 to 20 nm and 15 to 25 nm respectively. Ag and Au nanoparticles thus synthesized were then phase transferred into an organic solution using a cationic surfactant octadecylamine. Transmetallation reaction between hydrophobized silver nanoparticles and hydrophobized chloroaurate ions in chloroform resulted in the formation of gold nanoparticles.
Keywords: Biosynthesis; Nanomaterials; Phase transfer; Transmetallation